Analysis of Students' Critical and Creative Thinking Skills on the Application Of A Problem-Based Learning Model Contained with Etno-Science (Etno-PBL) - Patricia, Novita; Sumarni, Woro; Mursiti, Sri (International Journal of Active Learning, 2022)
The learning process in schools is considered not to focus on real-life problems that require critical and creative thinking skills from students. In addition, the learning carried out did not pay attention to the local culture that developed in the area. Therefore, this study aims to analyze students' critical and creative thinking skills after applying a problem-based learning model that contains ethnoscience. This study uses a mixed method with a sequential explanatory strategy. This research was conducted on students of class X MIPA SMAK Santo Thomas Aquinas Bengkayang, West Kalimantan, for the academic year 2021/2022. Test the validity of quantitative data and qualitative data using a concurrent triangulation strategy which was carried out at the same time. The results showed that the average score of critical and creative thinking skills was 77.7 and 75.9, respectively, with high levels, while the N-gain values were 0.57 (medium) and 0.72 (high). The conclusion is that ethnoscience-based problem-based chemistry learning in this study is effective in developing students' critical thinking and creative thinking skills.